2017
DOI: 10.1080/14786419.2016.1274888
|View full text |Cite
|
Sign up to set email alerts
|

A novel benzimidazole and other constituents with antiproliferative and antioxidant properties fromThymelaea microphyllaCoss. et Dur

Abstract: A new compound (microphybenzimidazole, 7) along with the six known compounds matairesinol (1), prestegane B (2), umbelliferone (3), daphnoretin (4), microphynolide A (5) and microphynolide B (6) were isolated from Thymelaea microphylla. The structures of the pure compounds were elucidated by spectroscopic and mass-spectrometric analyses, including 1D-, 2D-NMR, and HPLC-TOF/MS. Compounds 2 and 4, as well as three fractions (F6, F6-C5, and F6-W42) obtained from a 50% (v:v) CHCl:MeOH extract exhibited a selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Recently, we have reported the new benzimidazole and six known compounds with their antiproliferative and antioxidant activities from T. microphylla (11). We herein report the isolation and structural elucidation of three flavonoids from the chloromethanolic extract of T. microphylla.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Recently, we have reported the new benzimidazole and six known compounds with their antiproliferative and antioxidant activities from T. microphylla (11). We herein report the isolation and structural elucidation of three flavonoids from the chloromethanolic extract of T. microphylla.…”
Section: Introductionmentioning
confidence: 91%
“…It has been used in folk medicine for the treatment of wounds, erysipelas, skin cancer, pimples, and abscess (8). Several studies have shown that this species had remarkable antibacterial, antioxidant (9, 10), antiinflammatory (6), and antiproliferative (11) activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prestegane B is a natural compound isolated from Thymelaea microphylla , which exhibits a selective antiproliferative effect in C6 cells. It also has free radical scavenging property (Noman et al, ). Selenocysteine, a natural selenoamino acid, arrests S‐phase of the cell cycle by DNA damage via ROS and superoxide generation in U251 and U87 cells.…”
Section: Natural Product and Glioma Therapymentioning
confidence: 99%
“…Recently, phytochemicals have grabbed attention in the study of breast cancer therapy because of the strong antitumor activity and few adverse effects on patients. , Icariin, a flavanol glycoside, effectively causes apoptosis and suppresses migration through the SIRT6/NF-κB signal molecules in breast cancer cells . Daphnoretin, one of the main active ingredients of Daphne giraldii Nitsche, displays several pharmacological effects, e.g., antitumor effect, antioxidation effect, and anti-inflammation. One study reported that daphnoretin induced apoptosis and inhibited cell invasion and migration via the PI3K/AKT signal molecules in colon cancer HCT116 cells . Daphnoretin also displayed an obvious concentration-dependent suppression of HeLa cell proliferation.…”
Section: Introductionmentioning
confidence: 99%